The Effect of Treatment With Antiepileptic Drugs (Carbamazepine, Valproic Acid, Topiramate, And Their Combination) On Lipid Profile, C-Reactive Protein, And Renal Function in Iraqi Epileptic Patients - Yasir Radeef, Mohanad; Al-Shamma, Kassim (Tikrit Journal of Pharmaceutical Sciences, 2023)
This study was designed to evaluate the effect of treatment with antiepileptic drugs carbamazepine, valproic acid, topiramate, and their combination on lipid profile, C-reactive protein, and renal functions (urea & creatinine) in Iraqi epileptic patients. Ninety epileptic patients were participated in this study and their age ranged from (1-45) years. Seventy patients were previously diagnosed with epilepsy and received antiepileptic drugs for at least six months before this study (retrospective groups). The remaining patients were newly diagnosed with epilepsy (prospective groups). Twenty healthy subjects were selected to be a normal group for the purpose of comparison. The result showed an elevation in lipid profile after three months of treatment and this elevation was significant in serum total cholesterol, HDL-c, and LDL-c in retrospective groups and only significant for HDL-c in prospective groups. A clinically significant elevation in the level of CRP was observed in one patient and in seven patients after treatment with topiramate and combination therapy respectively. No significant differences were observed in renal function tests among the groups after treatment. In conclusion, the long term antiepileptic treatment increased the risk of atherosclerosis without significantly affecting renal functions